Production and loss of O2(1Δg) at atmospheric pressure using microwave-driven microplasmas. (29th December 2021) - Hoskinson, Alan R; Rawlins, Wilson T; Galbally-Kinney, Kristin L; Gong, Emily; Hopwood, Jeffrey
Abstract: We have used arrays of microwave-generated microplasmas operating at atmospheric pressure to generate high concentrations of singlet molecular oxygen, O2 ( 1 Δ g ), which is of interest for biomedical applications. The discharge is sustained by a pair of microstrip-based microwave resonator arrays which force helium/oxygen gas mixtures through a narrow plasma channel. We have demonstrated the efficacy of both NO and less-hazardous N2 O additives for suppression of ozone and associated enhancement of the O2 ( 1 Δ g ) yield. Quenching of O2 ( 1 Δ g ) by ozone is sufficiently suppressed such that quenching by ground state molecular oxygen becomes the dominant loss mechanism in the post-discharge outflow. We verified the absence of other significant gas-phase quenching mechanisms by measuring the O2 ( 1 Δ g ) decay along a quartz flow tube. These measurements indicated a first-order rate constant of (1.2 ± 0.3) × 10 −24 m 3 s −1, slightly slower than but consistent with prior measurements of singlet oxygen quenching on ground state oxygen. The discharge-initiated reaction mechanisms and data analysis are discussed in terms of a chemical kinetics model of the system.